Possible structure of mitigation-related modalities, procedures and guidelines for the enhanced transparency framework - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2017)
Article 13 of the Paris Agreement, agreed at the 21st Conference of the Parties to the United Nations Framework Convention on Climate Change (UNFCCC) in December 2015, calls for the adoption of an enhanced transparency framework for both mitigation action and support. This note presents a possible structure for the modalities, procedures and guidelines for the mitigation-related aspects of the enhanced transparency framework. The scope of the note includes reporting, technical expert review and multilateral consideration of progress, taking into account lessons learned from experience with reporting, review and other relevant processes under the UNFCCC and the Kyoto Protocol. The note aims to serve as a helpful reference for UNFCCC transparency negotiators, by flagging issues that will need to be addressed when Parties develop modalities, procedures and guidelines in this area, and by providing links to existing provisions or guidance for each topic